Pressure-stabilized structures of water-neon system under high pressure - Zhang, Jurong (2023)
Neon (Ne), as the fifth most abundant element in the universe, is rare to react with other elements by forming stable solid compounds. It is well known that pressure is a powerful tool to generate the compounds that are inaccessible at ambient pressure. In this work, we performed structure-searching simulations to examine stable compounds of Ne and H2O at a wide pressure range of 0-600 GPa. Our simulations identified two phases of H2ONe and H2ONe2 under high pressure. By employing chemical-bonding analysis, interestingly, we found that Ne-O interactions are comparable in strength to that of conventional hydrogen bond. Moreover, our molecular dynamic simulations indicate the diffusion behavior of hydrogen atoms within a fixed Ne-O lattice framework of H2ONe2 at high pressure and high temperature. These results provide the implications for the possible existence of pressure-stabilized H2ONe and H2ONe2 compounds viable in a variety of astronomical objects.